Alterações bioquímicas, crescimento e floração do pessegueiro 'Barboa' sobre porta-enxertos clonais - Oldoni, Chirlene Marcia (2018)
In the production of peach tree seedlings, the use of rootstocks with unknown genetic identity is frequent, and it is necessary to study and indicate the most compatible and superior agronomic rootstocks for the crop. The objective of this study was to identify the best clonal rootstocks for 'Barbosa' peach, in the edaphoclimatic conditions of the Rio Grande do Sul High Plateau, evaluating the growth in trunk diameter, biochemical changes (peroxidase activity, sugars and total soluble proteins) and flowering period. A total of 19 rootstocks (Barrier 1, Cadaman, Clone 15, Capdeboscq, Flordaguard, G x N9, Genovesa, Ishtara, I-67-52-4, Marianna 2624, Mexico F1, Mirabolano 29c, Nemared, Okinawa, Rigitano, Santa Rosa, Tsukuba 1, Tsukuba 2 and Tsukuba 3) propagated by herbaceous cutting, compared the combinations with the auto rooted crown. The design was randomized in three blocks, with one plant per plot. The evaluations were carried out during the first three cycles of vegetation, installed the Observation Unit spaced 5.0 m x 2.0 m, the plants were conducted in a double Y system without irrigation.The results showed that the rootstocks 'Marianna 2624', 'Clone 15', 'Nemared' and 'Santa Rosa', verified the mortality of all or most of the plants, show to be incompatible with 'Barbosa' peach. There was no significant correlation between the biochemical parameters (peroxidase activity, soluble sugars and proteins) and the growth of the trunk diameter above and below the graft point. Although the peroxidase activity has varied between the combinations, it is not possible to use this parameter alone, as a conclusive indicator of incompatibility. Plants grafted on 'Okinawa', 'Tsukuba 1', 'Tsukuba -2', 'Flordaguard' and 'Mexico F1' showed higher growth of rootstock and graft diameter, while lower growth on 'Barrier 1', 'G x N9', 'Genovesa' and 'Ishtara'. The Barbosa cultivar, propagated by herbaceous cutting, presents trunk growth similar to the best grafted combinations, revealing potential for the use of this type of seedlings when there are no restrictions related to pests and soil diseases. The beginning and the end of flowering can be influenced by the rootstock, varying with the climatic conditions of each cycle.